Non‐contrast‐enhanced peripheral angiography using a sliding interleaved cylinder acquisition. Issue 3 (9th September 2014) - Kwon, Kie Tae; Kerr, Adam B.; Wu, Holden H.; Hu, Bob S.; Brittain, Jean H.; Nishimura, Dwight G.
<x xml:space="preserve">Abstract</x> Purpose To develop a new sequence for non‐contrast‐enhanced peripheral angiography using a sliding interleaved cylinder (SLINCYL) acquisition. Methods A venous saturation pulse was incorporated into a three‐dimensional magnetization‐prepared balanced steady‐state free precession sequence for non‐contrast‐enhanced peripheral angiography to improve artery‐vein contrast. The SLINCYL acquisition, which consists of a series of overlapped thin slabs for volumetric coverage similar to the original sliding interleaved ky (SLINKY) acquisition, was used to evenly distribute the venous‐suppression effects over the field of view. In addition, the thin‐slab‐scan nature of SLINCYL and the centric‐ordered sampling geometry of its readout trajectory were exploited to implement efficient fluid‐suppression and parallel imaging schemes. The sequence was tested in healthy subjects and a patient. Results Compared to a multiple overlapped thin slab acquisition, both SLINKY and SLINCYL suppressed the venetian blind artifacts and provided similar artery‐vein contrast. However, SLINCYL achieved this with shorter scan times and less noticeable artifacts from k‐space amplitude modulation than SLINKY. The fluid‐suppression and parallel imaging schemes were also validated. A patient study using the SLINCYL‐based sequence well identified stenoses at the superficial femoral arteries, which were also confirmed with digital subtraction angiography. Conclusion Non‐contrast‐enhanced angiography using SLINCYL can provide angiograms with improved artery‐vein contrast in the lower extremities. Magn Reson Med 74:727–738, 2015. © 2014 Wiley Periodicals, Inc.